Effects of Various Agroecosystem Landscape on Arthropod Diversity: A Study Case in Kemiri Village, Jember, Indonesia: Effects Agroecosystem Landscape on Arthropod Diversity - Agung Sih Kurnianto; Nilasari Dewi; Ahmad Ilham Tanzil; Wildan Muhlison; Nur Laila Magvira; Luhur Septiadi (Journal of Tropical Life Science, 2022)
Agroecosystem landscapes have been studied extensively and it is known that there is a relationship between the spatial structure and the ecological processes. The composition of arthropods in the agroecosystem shows population differences that are closely related to the location. This study aims to isolate and analyze the interactions of arthropods and landscape structures and features of different agroecosystems landscapes in Kemiri, Jember, Indonesia. The plot method (20x20 m and 1x1 m dimension) was carried out to observe seedling, sapling, and tree (seedling h = 0-1.5 m, sapling h ≥ 1.5 m, tree D > 20 cm). The trees' species name, distance, number, and DBH were collected. Arthropods were sampled using PFT and SN methods. A vial (d=5 cm) was used for PFT, and SN was applied at a distance of 1x10 meters with 3 repetitions. Plants with the role of weeds in monoculture dominate (TA=45). Drosophilidae is the most recorded family in monoculture. Polyculture and agroforestry systems increased the diversity of arthropods in the vegetation, and Formicidae predominated by PFT (TA=28% and 81%, respectively). PCA shows the role of detrivores is mostly found in agroforestry, and herbivores dominate the monoculture. CCA shows that detrivore association in agroforestry is influenced by humidity, and herbivores are particularly interested in monoculture systems that provide high light, temperature, and wind intensity.